2010
DOI: 10.1111/j.1756-185x.2010.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical coronary artery disease in Asian rheumatoid arthritis patients who were in remission: a pilot study

Abstract: In our current pilot study with the limitation of small sample size, RA was not associated with an increased risk of CAD in our RA patients who were in remission. Larger studies of CAD in Asian RA patients are needed to confirm our current finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(46 reference statements)
2
3
0
Order By: Relevance
“…Ma, et al 46 reported that patients with RA who have active disease with longer disease duration have increased risk of cardiovascular events compared to the normal population, a finding that coincides with our previous ones. Meanwhile, Hosseinsabet, et al 47 found no correlation between CRP and CCS.…”
Section: Discussionsupporting
confidence: 90%
“…Ma, et al 46 reported that patients with RA who have active disease with longer disease duration have increased risk of cardiovascular events compared to the normal population, a finding that coincides with our previous ones. Meanwhile, Hosseinsabet, et al 47 found no correlation between CRP and CCS.…”
Section: Discussionsupporting
confidence: 90%
“…An earlier study investigated the presence of obstructive CAD in 47 patients with RA in stable remission using CTA 49. Incidence rates were similar to ours (19.1% for RA and 6.4% for controls versus 12% and 3%, respectively, in ours).…”
Section: Discussionsupporting
confidence: 85%
“…could demonstrate a reduction of IMT in RA patients, associated with a decrease in disease activity [45]. Also, in RA patients in remission (DAS-28 score below 2.60) with an average disease duration of three years, coronary artery disease was not increased compared to controls [51]. Secondly, discrepancies in IMT results might be explained by patient selection.…”
Section: Discussionmentioning
confidence: 99%